2006
DOI: 10.3168/jds.s0022-0302(06)72346-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Palm Kernel Meal and Corn Distillers Grains in Corn Silage-Based Diets for Lactating Dairy Cows

Abstract: The effects of increasing levels of solvent-extracted palm kernel meal (SPKM) and corn distillers dried grains (CDG) in corn silage-based diets on feed intake and milk production were examined in 2 experiments. In Experiment 1, 20 Holstein cows averaging 100 d in milk (DIM) (SD = 61.5) at the start of the experiment were utilized in an 11-wk randomized complete block design with 4 treatments in 5 blocks to study effects of increasing levels of SPKM in the diet. During a 3-wk preliminary period, cows were fed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
25
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 29 publications
8
25
1
Order By: Relevance
“…The results of the current study are difficult to compare with previous published studies, because no studies could be found where the effect of PKE supplementation was tested on the milk production of grazing dairy cows, even with PKE being a common raw material component in formulated dairy diets. However, the milk yield and 4% FCM of the current study are in agreement with the results obtained by Carvalho et al (2006).…”
Section: Production Parameters 421 Milk Yieldsupporting
confidence: 82%
See 4 more Smart Citations
“…The results of the current study are difficult to compare with previous published studies, because no studies could be found where the effect of PKE supplementation was tested on the milk production of grazing dairy cows, even with PKE being a common raw material component in formulated dairy diets. However, the milk yield and 4% FCM of the current study are in agreement with the results obtained by Carvalho et al (2006).…”
Section: Production Parameters 421 Milk Yieldsupporting
confidence: 82%
“…The milk fat and milk protein results of the current study concur to the results obtained by (Khalili and Sairanen, 2000) and (Carvalho et al, 2006). A review by Bargo et al (2003) reported that milk protein content was reduced by -0.06 percentage units with fibre-based concentrates compared with starch-based concentrates, with a milk protein response range from -0.21 to 0.05 percentage units.…”
Section: Milk Compositionsupporting
confidence: 80%
See 3 more Smart Citations